Effects of ethylenediaminetetraacetic acid, citric acid, and etidronic acid on root dentin mineral content and bond strength of a bioceramic-based sealer: A scanning electron microscopy-energy dispersive spectroscopy study - Ahmet Taşan; Esin Özlek (Tabriz University of Medical Sciences, 2024)
Background. This study assessed the impact of chelating agents, 17% ethylenediaminetetraacetic acid (EDTA), 10% citric acid (CA), and 18% etidronic acid (HEDP), on root dentin mineral content. Scanning electron microscopy-energy dispersive spectroscopy (SEM-EDS) was applied to analyze changes, and the push-out bond strength test was used to measure dentin adhesion of Well-Root ST, a bioceramic root canal sealer. Methods. A total of 80 extracted single-rooted lower premolar teeth were included in this study and randomly divided into four groups (n=20): group 1 (17% EDTA), group 2 (10% CA), group 3 (18% HEDP), and group 4 (distilled water, control). After irrigation and drying, SEM-EDS was applied to analyze eight samples from each group at coronal, middle, and apical root regions for mineral content and SEM images. The remaining 12 samples underwent a push-out bond strength test using Well-Root ST sealer and gutta-percha. Kruskal-Wallis and Dunn's tests were used for statistical analyses. Results. Statistically significant differences were found between groups (P<0.05). SEM-EDS showed significant differences in C, O, Ca, P, and Ca/P content, with no significant differences in Na and Mg. Push-out bond strength was significantly higher in the 17% EDTA, 10% CA, and 18% HEDP groups compared to the control group, with no significant differences between chelating agents. Conclusion. Chelating agents altered root dentin mineral content and improved the adhesive properties of the bioceramic sealer. These findings highlight the importance of considering the selection and use of chelating agents in the clinical practice for root canal treatment.